THE SITUATION OF HESITATION BEHAVIOR OF TAKING COVID-19 VACCINATION AND RELATED FACTORS OF PEOPLE LIVING IN DICH VONG, CAU GIAY, HANOI IN 2022 (Vietnam Journal of Community Medicine, 2024)
Background: “Immunization hesitancy” was a fairly new concept developed by SAGE to measurethe rate of hesitation for people to participate in vaccination.Research objectives: Determining the state of hesitancy to vaccinate against COVID-19 and somerelated factors of people in Dich Vong ward, Cau Giay district, Hanoi, in 2022.Research methodology: This study was conducted with a cross-sectional method, designedquestionnaire, and in-depth interview.Research result: The assessment has found that the percentage of people who have hesitatingbehavior toward COVID-19 vaccination of research subjects in the Dich Vong ward is higher thanits percentage at the national level. The percentage of research subjects who have hesitating behaviortoward COVID-19 vaccination among the high-risk group of COVID-19 is 25%, especially in thegroup living in places with more than 5 cases of COVID-19 was 36,3%. There is a difference in thepercentage of hesitating behavior toward COVID-19 among high-risk groups with middle & lowrisk groups. The associated factors with hesitating behavior toward COVID-19 in the Dich Vongward, Cau Giay district, include occupation, the number of COVID-19 in the residence area andattitude towards the proposal of fee collection of COVID-19 vaccination.Conclusion & recommendation: The research shows that the rate of DD in the study subjectsin the Dich Vong ward is higher than the national rate. Therefore, it is necessary to strengthencommunication and mobilize people to get vaccinated against COVID-19. At the same time, developcommunication programs to improve people’s knowledge and develop training programs for wardhealth workers and population leaders.
Keywords: COVID-19, hesitate of COVID-19 vaccination, COVID-19 vaccination, COVID-19 pandemic, side effects of COVID-19 vaccine.